2009
DOI: 10.1007/s11199-009-9648-y
|View full text |Cite
|
Sign up to set email alerts
|

Bad Woman, Bad Victim? Disentangling the Effects of Victim Stereotypicality, Gender Stereotypicality and Benevolent Sexism on Acquaintance Rape Victim Blame

Abstract: Based on the assertion that previous research may have inadvertently confounded two stereotypes, we considered the impact of benevolent sexism on rape victim blame in the context of independent manipulations of gender and the perceived genuineness (victim stereotypicality) of an acquaintance rape victim. We predicted that for blame, benevolent sexism may be independently positively associated with gender and victim counter-stereotypicality. Following pilot work, 120 Australian undergraduates read an acquaintan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
6
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(133 citation statements)
references
References 46 publications
(96 reference statements)
5
114
6
7
Order By: Relevance
“…It may also be that the effects of gender role attitudes itself are moderated by additional variables. It was found that the perception of victims' intentions and the perception of victims as behaving appropriately versus inappropriately act as moderating variables between gender role attitudes and rape blame attribution, which would indicate a more moderate influence of gender role attitudes than assumed (Abrams, Viki, Masser, & Bohner, 2003;Masser, Lee, & McKimmie, 2010).…”
Section: Gender Role Attitudesmentioning
confidence: 94%
“…It may also be that the effects of gender role attitudes itself are moderated by additional variables. It was found that the perception of victims' intentions and the perception of victims as behaving appropriately versus inappropriately act as moderating variables between gender role attitudes and rape blame attribution, which would indicate a more moderate influence of gender role attitudes than assumed (Abrams, Viki, Masser, & Bohner, 2003;Masser, Lee, & McKimmie, 2010).…”
Section: Gender Role Attitudesmentioning
confidence: 94%
“…Men usually score higher on sexism scales (Masser, Lee, & McKimmie, 2010), but women may also have sexist reactions towards non-traditional victims, especially when they succeed in typically male professions (Parks-Stamm, Heilman, & Hearns, 2008). Based on two studies using German community samples, Becker (2010) tried to explain why women endorse in hostile and benevolent sexist attitudes.…”
Section: Ambivalent Sexismmentioning
confidence: 99%
“…Further, past studies using designs similar in complexity to the present study have utilised comparable or smaller sample sizes than ours (e.g. Masser et al, 2010 who reported a 2 x 2 independent groups design with BS as a measured variable) while detecting significant and theoretically consistent effects. Thus, our sample size is adequate given the complexity of the analyses reported.…”
Section: Methods Participantsmentioning
confidence: 73%
“…Study 2, Becker, 2010) common in the ambivalent sexism and subtyping literatures, even in studies with designs of a complexity similar to the one reported here (e.g. Masser et al, 2010).…”
Section: Methods Participantsmentioning
confidence: 74%
See 1 more Smart Citation